Adenomatous hyperplasia of the rete testis: Not a true hyperplasia, just proliferation! - Ozgur, Tumay; Akin, Mehmet Mustafa; Gokce, Hasan; Davarci, Mursel (Contemporary Oncology/Współczesna Onkologia, 2013)
There are several tumor-like lesions and miscellaneous neoplasms of the rete testis. We present a case with adenomatous hyperplasia of the rete testis (AHRT). The patient was 24 years old with undescended testis and was referred to our hospital. There were no clinical or endocrine abnormalities. Cryptorchidism was unilateral and the other testis was normal. Right orchiectomy was performed and sent to the pathology laboratory for examination. Morphologic and immunohistochemistry findings confirmed the diagnosis of AHRT in this case. The patient’s postoperative course continues uneventfully. AHRT is a rare lesion and can be confused with malignancy. It is incidentally detected in microscopic investigation. It may present as a very small lesion detected in microscopic examination or a solid-cystic mass lesion which is macroscopically evident. Clinical history, localization, histologic features and immunohistochemistry are criteria for differentiating these lesions. We present this rare case for both surgeons and pathologists due to its importance as it can be confused with malignancy.